Novelties in Compositae from Vellozo’s Florae Fluminensis - Sitowski, Aline; Teles, Aristônio Magalhães; Antar, Guilherme Medeiros; Barêa Pastore, José Floriano (Phytotaxa, 2022)
The identity of one Compositae name from Vellozo’s Florae Fluminensis, Chrysocoma adpressa, is revised with taxonomic notes, leading to one new combination, Lucilia adpressa, and a new synonym, L. lycopodioides under L. adpressa. We provided typifications for all not yet typified names involved, with the designation of five lectotypes and one epitype. Additionally, we included a nomenclatural and taxonomic discussion, illustrations and a distribution map for the studied species.